2021
DOI: 10.3389/fimmu.2021.795574
|View full text |Cite
|
Sign up to set email alerts
|

Risk for Cardiovascular Adverse Events Associated With Sphingosine-1-Phosphate Receptor Modulators in Patients With Multiple Sclerosis: Insights From a Pooled Analysis of 15 Randomised Controlled Trials

Abstract: BackgroundAll agents engaging sphongosine-1-phospate receptors (S1PRs) will have some cardiovascular effect. This study aimed to elucidate the risk of cardiovascular adverse events (AEs) in patients with multiple sclerosis (MS) treated with S1PR modulators (S1PRMs).MethodsWe systematically searched the PubMed, EMBASE, and Cochrane Library databases for randomised controlled trials (RCTs) published through January 5, 2021. Relative risks (RRs) and 95% confidence intervals (CIs) were calculated using the random-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…This could be attributed to the associated adverse effects. A pooled analysis of 15 randomized control trials with S1PRMs showed an increased risk of bradyarrhythmia and hypertension in MS patients [ 31 ]. As a result, clinicians assess the benefit-to-risk ratio before prescribing S1PRMs.…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to the associated adverse effects. A pooled analysis of 15 randomized control trials with S1PRMs showed an increased risk of bradyarrhythmia and hypertension in MS patients [ 31 ]. As a result, clinicians assess the benefit-to-risk ratio before prescribing S1PRMs.…”
Section: Discussionmentioning
confidence: 99%
“…They included 17 studies including 13,295 patients and found that these S1P receptor modulators were associated with an increased risk of overall cardiovascular events (risk ratio (RR), 2.21; 95% CI, 1.58–3.10), primarily bradyarrhythmia (RR, 2.92; 95% CI, 1.91–4.46) and hypertension (RR, 2.00;95% CI, 1.49–2.67). However, in subgroup analysis, ozanimod was only associated with hypertension, but not bradyarrhythmia 102 . Notably, there seems to be no increased risk of MACE with the use of S1P receptor modulators.…”
Section: Risk Of Cardiac Conduction Abnormalities With Smdsmentioning
confidence: 85%
“…101 Fingolimod is a nonselective S1P receptor modulator, and consequently, it has been shown consistently to increase the risk of bradycardia in most clinical trials among patients with multiple sclerosis. 102 In three phase 3, placebo-controlled trials in patients with multiple sclerosis, after the first dose, fingolimod produced a transient, dose-dependent decrease in mean heart rate after 4-5 h, with a maximum reduction of 8-11 beats per minute below the baseline. 103 Symptomatic bradycardia at treatment initiation was reported in 0.6% (fingolimod 0.5 mg) and 2.1% (fingolimod 1.25 mg) of patients, whereas AV block was less frequent: Mobitz type I, second-degree AV block occurred in 0.2% and 1% of patients, respectively.…”
Section: Evidence From Non-ibd Imids Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As of now, they do not have any major safety concerns although do have some known off target effects. For example, by modulating S1P receptor in the myocardium, ozanimod has chronotropic effects causing a transitory dose-dependent bradycardia [42]. They show potential for use biologic-naı ¨ve and exposed patients and are a potential alternative therapeutic option in UC patients with moderate disease.…”
Section: Integrating Sphingosine 1-phosphate Receptor Modulators Into...mentioning
confidence: 99%